Amine-functionalized porous organic polymers for carbon dioxide capture. Issue 17 (13th July 2022) - Sekizkardes, Ali K.; Wang, Ping; Hoffman, James; Budhathoki, Samir; Hopkinson, David
Abstract : Amine functionalization methods in porous organic polymers for CO2 capture applications. The figure was created by Michael J. Gipple. Abstract : Recent developments in CO2 capture using porous organic polymers (POPs) have received accrescent attention due to their sorbent properties such as high CO2 uptake capacity and selectivity, tunable chemical structure and permanent porosity. POPs are constructed using two and/or three-dimensional organic monomers (building blocks) linked to each other through covalent bonding, creating high porosity. The pore structure in POPs is exceptionally stable, which leads to their cyclable CO2 adsorption performance. However, POPs generally suffer from low CO2 uptake and selectivity due to their interaction with CO2 in physisorption limits (20–40 kJ mol −1 ). Similar to that in other physisorbents, the CO2 uptake capacity of POPs further decreases under humid conditions. Pursuant to these limitations, amine functionalization in POPs has resulted in enhanced CO2 uptake performance with improved CO2 selectivity over non-polar gases such as N2 . More importantly, several types of amine-functionalized POPs showed that the CO2 uptake could remain intact under humid conditions such as in post-combustion flue gas. This review article covers recent developments in amine-functionalized porous organic polymers. Three main categories of amine functionalization, such as direct amine synthesis, amine impregnation and amine grafting, were investigated in detail by considering the effect of amines on the sorbent properties and CO2 capture performance of POPs. The recent findings in amine-functionalized POPs were investigated including porous polymeric networks (PPNs), covalent organic frameworks (COFs), amine linked POPs, hyper-crosslinked polymers (HCPs), conjugated microporous polymers (CMPs), benzimidazole linked polymers (BILPs), porous aromatic frameworks (PAFs) and polymers of intrinsic microporosity (PIMs).